Developing Workplace Skills via Employer Projects - Ali, M.F.M; Pereira, E.A; Phang, S.S.; Vijayaratnam, P.A. (INTI International University, 2018)
Employer engagement in education is gaining momentum in universities today via activities such as employer projects, internship, workplace visits, etc. The research will explore the effectiveness of an employer relations project in developing workplace skills among pre-university students in a private university. The paper utilizes a mixed method approach and the primary method is a questionnaire to determine students’ attitude towards the project. The qualitative study will probe deeper into student experiences towards the task. This was done via focus group interviews. A key finding will be the importance of small group collaboration in developing students’ soft skills and personal development.